2019
DOI: 10.1093/cid/ciz614
|View full text |Cite
|
Sign up to set email alerts
|

Common Behaviors and Faults When Doffing Personal Protective Equipment for Patients With Serious Communicable Diseases

Abstract: Background The safe removal of personal protective equipment (PPE) can limit transmission of serious communicable diseases, but this process poses challenges to healthcare workers (HCWs). Methods We observed 41 HCWs across 4 Ebola treatment centers in Georgia doffing PPE for simulated patients with serious communicable diseases. Using human factors methodologies, we obtained the details, sequences, and durations of doffing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
0
24
0
3
Order By: Relevance
“…The rationale was simple. Prior research demonstrates that using unfamiliar or increasingly complex PPE increases the risk of selfcontamination 3 . Consequently, training for healthcare workers (HCW) focused on ensuring proper donning and doffing techniques with familiar, well-rehearsed PPE procedures.…”
mentioning
confidence: 99%
“…The rationale was simple. Prior research demonstrates that using unfamiliar or increasingly complex PPE increases the risk of selfcontamination 3 . Consequently, training for healthcare workers (HCW) focused on ensuring proper donning and doffing techniques with familiar, well-rehearsed PPE procedures.…”
mentioning
confidence: 99%
“…Second, what allows our hospital to maintain baseline preparedness for novel high-consequence pathogens is that our standard PPE for managing these patients only includes components that are already familiar to our HCWs. This decision was made based on evidence demonstrating that additional PPE complexity is associated with risks of self-contamination during doffing (12). This approach is also consistent with prior evidence from SARS-CoV-1 suggesting that transmission occurs by the droplet or contact route (13).…”
Section: Discussionmentioning
confidence: 71%
“…11 The study done by Mumma JM, et al assessing common behavioral faults during doffing found that the most frequent steps leading to maximal non-compliance involved removing the outermost garment, boot covers, and respirator hood apart from hand hygiene. 26 Ensuring hand hygiene with alcohol based sanitizers with a minimum contact time of 20 seconds, at every step of removal of each item of PPE is crucial. 7 This could be ensured with the help of audible alarms or music for a requisite duration (20 seconds) after pressing the foot operated sanitizer systems.…”
Section: Human Behaviour and Compliance To Protocolsmentioning
confidence: 99%